2013
DOI: 10.1364/ao.52.007769
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of numerical methods for the mode analysis of laser beams

Abstract: We present a comparative study of four numerical methods to detect the mode content of a laser beam from, at most, two intensity images. The techniques are compared regarding temporal effort, stability, and accuracy, using the example of three multimode optical fibers that differ in the number of supported modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 31 publications
(41 reference statements)
0
45
0
Order By: Relevance
“…As discussed in [13] and [14], the uncertainty is only the sign of the relative phase for the three-mode fiber, the case of this paper. It means that the modal spectra illustrated in Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As discussed in [13] and [14], the uncertainty is only the sign of the relative phase for the three-mode fiber, the case of this paper. It means that the modal spectra illustrated in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…And it can even be accelerated to the msregime by using high speed camera for analyzing MI [4]. In brief, this method utilizes a mapping of the twodimensional field distribution onto the one-dimensional space of fiber eigenmodes and numerically extracts the modal coefficients by some algorithms, such as Gerchberg-Saxton (GS) algorithm [12], line-search (LS) algorithm [13], and simplex-search (SS) algorithm [4]. However, the GS algorithm suffers from relatively long computation time and the other two algorithms are based on searching the minimum, which have high dependence on the initial values and are easily trapped onto local minima instead of the global one.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that for superposition with three or less modes already the intensity distribution of the near field plane is sufficient to reconstruct the modal power spectrum. 12 For the determination of the relative phase delay additional information about the intensity distribution in the far field plane is required to get the correct sign of the phase distribution. 12 Unfortunately, also in this case some ambiguity remains concerning centrosymmetrical beams, e.g.…”
Section: Numerical Mode Analysismentioning
confidence: 99%
“…12 For the determination of the relative phase delay additional information about the intensity distribution in the far field plane is required to get the correct sign of the phase distribution. 12 Unfortunately, also in this case some ambiguity remains concerning centrosymmetrical beams, e.g. perfectly ring-shaped right-and left-handed vortex beams as their intensity distributions remain the same during propagation.…”
Section: Numerical Mode Analysismentioning
confidence: 99%
“…Such wavefront sensing techniques rely on the ability to measure the phase of light which can only be indirectly inferred from intensity measurements. Methods to do so include ray tracing schemes, intensity measurements at several positions along the beam path, pyramid sensors, interferometric approaches, computational approaches, the use of non-linear optics, computer generated holograms (CGHs), meta-materials and polarimetry [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Perhaps the most well-known is the Shack-Hartmann wavefront sensor [22,23].…”
Section: Introductionmentioning
confidence: 99%